PROFIL VERTIKAL DAN LUAS BIDANG DINAMIKA HARIAN GRADIEN SUHU UDARA DI ATAS PERMUKAAN LAHAN TERBUKA, LAHAN BERVEGETASI DAN PERMUKAAN ASPAL - Givraldi Kumentas; Donny Wenas; Alfrie Rampengan; Christophil Medellu (Fakultas Matematika Ilmu Pengetahuan Alam dan Kebumian, Universitas Negeri Manado, 2021)
This study aims to determine the temporal function model, spatial temperature and dynamic models of air temperature gradients over the surface of open land, vegetated land, and asphalt surface. The research location is at the State University of Manado in the hills of Tonsaru South Tondano, Minahasa Regency. The research methodology was carried out on three transects at nine altitude positions for 24 hours of measurement time, measuring positions ranging from the ground level to 0cm, 10cm, 30cm, 60cm, 100cm, 150cm, 220cm, 300cm, to 400cm. Data processing carried out in this study is by entering data on air temperature, the measured ground surface into the Matlab application. It can be shown that temporal changes and vertical spatial variations in air temperature show different but relatively the same curve shapes in hot weather conditions during the day, expressed by using a mathematical model of the Fourier function and daily dynamics of air temperature gradients on various land surfaces is influenced by the process of heat absorption and thermal emission processes from the soil in various lands.